2021
DOI: 10.33774/chemrxiv-2021-t94rt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determining the Self-Limiting Electrospray Deposition Compositional Limits for Mechanically Tunable Polymer Composites

Abstract: Electrospray deposition (ESD) is a versatile micro/nano coating technology that utilizes the competition between surface charge of a droplet and its surface tension to create monodisperse generations of micro/nano droplets. ESD can deposit uniform thin films by including dilute solutes in these droplets. One mode of ESD, self-limiting electrospray deposition (SLED), has been shown to exist when glassy polymers are sprayed in a volatile solvent below the polymer glass transition temperature (Tg). This leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In addition, the spray of insulating polymers produces thicknesslimited films in which the charge accumulation repels incoming spray droplets. 4,11,12 This self-limiting behavior enables the conformal coating of complex 3D surfaces. 13 Recent work from our group has shown that methylcellulose (MC) forms a selflimiting coating with a unique nanowire architecture when processed by ESD from water : ethanol solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the spray of insulating polymers produces thicknesslimited films in which the charge accumulation repels incoming spray droplets. 4,11,12 This self-limiting behavior enables the conformal coating of complex 3D surfaces. 13 Recent work from our group has shown that methylcellulose (MC) forms a selflimiting coating with a unique nanowire architecture when processed by ESD from water : ethanol solutions.…”
Section: Introductionmentioning
confidence: 99%